Digital futures for learning speculative methods and pedagogies - Ross, Jen (New York Routledge, 2023)
"Digital Futures for Learning offers a methodological and pedagogical way forward for researchers and educators who want to work imaginatively with 'what's next' in higher education and informal learning. Today's debates around technological transformations of social, cultural, and educational spaces and practices need to be informed by a more critical understanding of how visions of the future of learning are made and used, and how they come to be seen as desirable, inevitable, or impossible. Integrating innovative methods, key research findings, engaging theories, and creative pedagogies across multiple disciplines, this book argues for and explores speculative approaches to researching and analysing post-compulsory and informal learning futures-where we are, where we might go, and how to get there"--
How learning futures are made -- Complexity, emergence and learning futures -- Speculative approaches to research and teaching -- Teaching at scale, automation and a speculative teacherbot -- Working with digital futures for learning through student-generated open educational resources -- Artcasting and digital cultural heritage engagement futures -- Telling data stories to explore the future of surveillance -- Speculative methods and digital futures research -- Speculative pedagogies and teaching -- Keeping learning futures moving.
Includes bibliographical references and index.
Keywords: Education, Higher -- Effect of technological innovations on; Education, Higher -- Forecasting; Non-formal education -- Effect of technological innovations on; Non-formal education -- Forecasting